2022
DOI: 10.3390/biomedicines10061271
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Profiling of Glucocorticoid (NR3C1) and Mineralocorticoid (NR3C2) Receptor Polymorphisms before Starting Therapy with Androgen Receptor Inhibitors: A Study of a Patient Who Developed Toxic Myocarditis after Enzalutamide Treatment

Abstract: Enzalutamide is a nonsteroidal inhibitor of the androgen receptor (AR) signaling pathway and is used to treat patients with metastatic castration-resistant prostate cancer. However, the risk of cardiovascular-related hospitalization in patients with no contraindications for the use of enzalutamide is about 1–2%. To date, the underlying molecular basis of this has not been established. The androgen receptor, glucocorticoid receptor (GR) and mineralocorticoid receptor (MR) are nuclear receptors that share struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Furthermore, a case report showed that the administration of abiraterone acetate to a 70-year-old male resulted in cardiovascular dysfunction and syncope [77] Similarly, ventricular repolarization is reported as a possible adverse effect of enzalutamide therapy in male patients with hypogonadism [88]. Furthermore, enzalutamide could cause toxic myocarditis by affecting a co-regulator that interacts with and hyperactivates the rs5522-mutated mineralocorticoid receptor [89]. A randomized, double-blind, phase II study documented high grades of cardiac adverse events such as myocardial infarction, congestive HF, and atrial fibrillation upon treatment with enzalutamide [90].…”
Section: Cardiotoxicity Of Second-generation Anti-androgensmentioning
confidence: 99%
“…Furthermore, a case report showed that the administration of abiraterone acetate to a 70-year-old male resulted in cardiovascular dysfunction and syncope [77] Similarly, ventricular repolarization is reported as a possible adverse effect of enzalutamide therapy in male patients with hypogonadism [88]. Furthermore, enzalutamide could cause toxic myocarditis by affecting a co-regulator that interacts with and hyperactivates the rs5522-mutated mineralocorticoid receptor [89]. A randomized, double-blind, phase II study documented high grades of cardiac adverse events such as myocardial infarction, congestive HF, and atrial fibrillation upon treatment with enzalutamide [90].…”
Section: Cardiotoxicity Of Second-generation Anti-androgensmentioning
confidence: 99%